Analisis Khiyar Syarat dan Khiyar Aib dalam Transaksi Jual Beli Pakaian di Pasar Tradisonal Bungi Kab. Pinrang - Ibrahim, Nurafida (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2024)
This research aims to find out how the practice of khiyar conditions and khiyar aib in clothing buying and selling transactions at the Bungi District traditional market. Duampanua District. Pinrang? and how to analyze sharia economic law on the application of khiyar conditions and khiyar aib in clothing buying and selling transactions at the traditional market in Bungi District. Duampanua District. Pinrang?The type of research used is field research which is descriptive qualitative in nature. The research approach used is normative and sociological. The data in this research was obtained from primary data and secondary data. Data collection techniques are carried out through observation, interviews and documentation, complemented by data analysis techniques using data reduction, data presentation and drawing conclusions.The results of this research explain that the practice of khiyar terms and khiyar aib in clothing buying and selling transactions at the Bungi market has implemented khiyar terms and khiyar aib in the sense that when an error occurs in a product containing a fault it can be returned or exchanged for other goods but not by canceling the transaction with a return. money that has been paid, while in other transactions the cancellation of the sale and purchase transaction is implemented by returning the full amount of money that has been paid as previously agreed. In other transactions, there are some sellers who only care about profits without paying attention to the risks they have created which of course can be detrimental to the buyer. Even though it has been explained in the consumer protection law no. 8 of 1999 there are still those who violate and break the rules. Based on the analysis of sharia economic law on the application of khiyar terms and khiyar aib in clothing buying and selling transactions at the Bungi traditional market, the implementation of the transaction is in line with the principles of sharia economic law where there is an agreement at the beginning of the transaction between the two parties. In this way, sellers and buyers in buying and selling apply honesty.